Conductive inks of graphitic nanoparticles from a sustainable carbon feedstock - Hof, Ferdinand; Kampioti, Katerina; Huang, Kai; Jaillet, Christèle; Derré, Alain; Poulin, Philippe; Yusof, Hisham; White, Thomas; Koziol, Krzysztof K.; Paukner, Catharina; Pénicaud, Alain (Elsevier, 2016)
Microwave plasma splitting of biogas to solid carbon forms is a promising technique to produce large quantities of sustainable carbon based nano materials. Well defined graphitic nano carbons have been produced exhibiting graphene multilayers in turbostratic packing. After heat treatment, the purified material has been used to formulate stable, aqueous dispersions. These dispersions are used directly as inks, allowing the preparation of conductive membranes with remarkable resistivity. Nano carbons derived by plasma processes constitute a promising alternative to carbon black because they can be prepared from renewable sources of methane or natural gas, are calibrated in size, exhibit high conductivity, and have promising perspectives for chemical and material science purposes.